MODERN CLINICAL AND DIAGNOSTIC APPROACHES TO THE EARLY DETECTION AND TREATMENT OF UROLOGICAL DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Urological diseases remain a significant global health burden due to their high prevalence, progressive nature, and substantial impact on quality of life. Early detection and timely treatment are critical factors in improving clinical outcomes and reducing long-term complications. This article provides a comprehensive analysis of modern clinical and diagnostic approaches applied in the early detection and management of urological diseases. Particular attention is given to the integration of advanced imaging techniques, laboratory biomarkers, molecular diagnostics, and minimally invasive diagnostic procedures in contemporary urological practice. The role of evidence-based clinical assessment, risk stratification, and personalized treatment strategies is also emphasized. Furthermore, the article highlights the importance of multidisciplinary collaboration and the implementation of innovative technologies, including artificial intelligence–assisted diagnostic systems, in enhancing diagnostic accuracy and therapeutic decision-making. The findings underscore that the adoption of modern diagnostic and clinical approaches significantly improves early detection rates, optimizes treatment outcomes, and contributes to the development of individualized, patient-centered care in urology.